With x , y are non-negative real numbers satisfying this set of equations, find x + y :
{ x ( x 2 + y 2 ) = y 4 ( y 2 + 1 ) 4 x 2 + 5 + y 2 + 3 = 5
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Good solution!
Is there a way to solve for y without comparing y and 1 ? It’s just unnatural.
Problem Loading...
Note Loading...
Set Loading...
Assume that y = 0 . The first equation with y = 0 implies that x = 0 , but x = y = 0 does not satisfy the second equation, so y = 0 .
Let x = k y . From the first equation ( x 2 + y 2 ) = y 4 ( y 2 + 1 ) , replace x with k y will change it to k y ( k 2 y 2 + y 2 ) = y 4 ( y 2 + 1 ) or k 3 y 3 + k y 3 = y 6 + y 4 , which leads to y 3 ( k 3 + k ) = y 3 ( y 3 + y ) . We have proven that y = 0 above, so k 3 + k = y 3 + y .
Next, we will compare y with k :
*If k < y then k 3 < y 3 , implying k 3 + k < y 3 + y , which is not correct.
*If k > y then k 3 > y 3 , implying k 3 + k > y 3 + y , which is not correct.
*If k = y then k 3 = y 3 , implying k 3 + k = y 3 + y , this matches what we have proven above.
Because of this, k = y , but we let x = k y at the beginning, so x = y 2 .
From the second equation 4 x 2 + 5 + y 2 + 3 = 5 , replace x with y 2 will change it to 4 y 4 + 5 + y 2 + 3 = 5
We know that both y 4 and y 2 are always non-negative for all numbers y , so this time we will compare y 2 with 1:
*If y 2 < 1 then y 4 < 1 , so 4 y 4 + 5 < 9 and y 2 + 3 < 4 , implying 4 y 4 + 5 + y 2 + 3 < 5 , which is not correct.
*If y 2 > 1 then y 4 > 1 , so 4 y 4 + 5 > 9 and y 2 + 3 > 4 , implying 4 y 4 + 5 + y 2 + 3 > 5 , which is not correct.
*If y 2 = 1 then y 4 = 1 , so 4 y 4 + 5 = 9 and y 2 + 3 = 4 , implying 4 y 4 + 5 + y 2 + 3 = 5 , this is correct.
So y 2 = 1 , we know that x = y 2 = 1 as proven above, and from y 2 = 1 , we also know that y = 1 because y is not a negative number.
Final result: x + y = 1 + 1 = 2 .